Efficacy of feed-based genome-free bacterial vaccine against Aeromonas hydrophila infection in red tilapia (Oreochromis sp.) - Mohd Ali, Nur Shidaa; Ngalimat, Mohamad Syazwan; Lim, Boon Chuan; Hsu, Chia-Chen; Salleh, Annas; Nazarudin, Muhammad Farhan; Md Yasin, Ina Salwany; Azmai, Mohammad Noor Amal (Multidisciplinary Digital Publishing Institute (MDPI), 2024)
Aeromonas hydrophila causes motile Aeromonas septicemia (MAS), a disease with a high mortality rate in tilapia culture. Feed-based vaccines with the incorporation of inactivated whole-cell bacteria into the feed offer promising tools to control MAS. Currently, the incorporation of genome-free bacteria as bacterial vaccine through the implementation of SimCells® technology into the feed has become a particular interest. Background/Objectives: This study investigates the efficacy of a feed-based vaccine incorporating genome-free A. hydrophila (FBV-GFAH) against MAS infection in red tilapia. Methods: The vaccine was prepared and delivered at 5% fish body weight for three consecutive days in weeks 0 (prime vaccination) and 2 (first booster vaccination), orally. Throughout a five-week experimental period, the immune-related genes (IL-1β, MHC-II, CD4, IgT, and IgM) expression in the hindgut and head kidney of the fish was determined using RT-qPCR assay. Lysozyme (serum) and overall IgM (serum, gut lavage, and skin mucus) productions were also detected. Results: Fish vaccinated with FBV-GFAH showed a significant (p ≤ 0.05) improvement in relative percent survival compared with unvaccinated fish following bacterial challenge. FBV-GFAH induced the expression of immune-related genes in the hindgut and head kidney, especially after booster vaccination. Furthermore, serum lysozyme activity and overall IgM production in serum, skin mucus, and gut lavage were also significantly (p ≤ 0.05) improved in the FBV-GFAH vaccinated fish than the unvaccinated fish. Conclusions: This study showed that FBV-GFAH is a promising feed-based vaccine technology to control MAS in cultured tilapia. © 2024 by the authors.